The governmental support of the light industry in modern integration condition - Ukubassova, G.S.; Toksanova, A.N.; Galieva, A.Kh.; Amirbekova, A.B. (BUKETOV BUSINESS REVIEW, 2019)
Light industry is associated with many related industries and serves the entire national economic complex. The main feature of the light industry is a fairly quick return of funds invested in production and a quick change in the range of products that are produced, with «minimal» costs. Light industry as a branch of the economy is directly involved in the formation of state budgets. It combines a large number of industries, among the main ones are clothing, footwear, textile, leather, and fur. The largest share in the structure of light industry is occupied by the products of the clothing and textile industries. The support of small and medium businesses by the state remains an important and necessary tool that directly affects the growth of the economy and the welfare of the population. Foreign experience shows that the development of the light industry sector involves active government support, expressed in preferential taxation, attracting investment, stimulating the export of finished products, etc. This paper presents the author's presentation on global trends in the development of markets and light industry enterprises. Moreover, the individual trends of the global textile market at the present stage has been analyzed. The world experience of state support of light industry is summarized.